Evolución tectonosedimentaria de los depósitos plio-pleistocenos del Valle Central entre los 36°40´s y los 38°50´s Chile - Anavalon, Anibal (2017)
The Central Depression or Central Valley of south-central Chile extends in a N-S direction between the Coastal Range and the Andean Cordillera from Santiago to Chiloé island. It is filled with tertiary volcanic and sedimentary units of continental and marine origin (García, 1986). Plio-Pleistocene fluvial deposits are exposed in the Central Valley and also in the western Andes and eastern Coastal Range (Marangunic, 1970). In this work we carried out sedimentologic stratigraphic and geochronologic studies (U-Pb on detrital zircons) in order to determine the age, sedimentary environment, correlation and relation of this deposits with the uplift of the Andean and Coastal ranges.